Suture Material in Ancient Ayurveda and Modern Science - Trivedi, Diksha; Gupta, Rajesh (International Research Journal of Ayurveda & Yoga, 2021)
Acharya Sushruta father of ancient surgery has described Ashtvidh Shastra Karma (8 surgical procedures) in Sushruta Samhita they are as follows Chedana (Excision), Bhedna (Incision), Lekhana (Scraping), Vedhan (Puncturing), Eshan (Probing), Visravan (Evacuating), Seevan (Suturing), Aharay (Extraction) . Among Ashtvidh Shastra Karma, Seevan Karma (Suturing) is primarily important. Acharyas described Seevan Dravyas which are required for Seevan Karma i.e. Seevan Sutra and Seevan Suchi. For the purpose of proper wound healing good surgical practice should be applied and for proper suturing one should practice it with ideal techniques. It gives better result for wound healing. Basics of suturing which he described years back are still followed. Ayurvedic acharyas was very well known to the methods of suturing and its importance in practice and described well in various classical literature of Ayurveda. In modern day surgical practices, we all follow the same principle without change. Surgical suture is a medical device used to hold body tissues together after an injury or surgery. Suturing is the closuring technique of surgical as well as the traumatic wound and also final step of every surgical procedure. Sutures are used by your doctor to close wounds to your skin or other tissues.